Microorganisms Isolated fromMoroccan Olive-Mill Wastes: Screening of Their Enzymatic Activities for Biotechnological Use - Misbah, Asmae; Aouine, Mouna; Raouan, Safae Er; Lekbach, Yassir; Ettadili, Hamza; Koraichi, Saad Ibnsouda; Jouti, Mohamed Ali Tahri (European Scientific Journal, ESJ, 2019)
In this study, three samples of olive oil wastes: Olive Rinse Water (OR), Olive Mill Wastewater (OM) and Olive Pomace (OP), which were collected from an olive oil mill located at Fez-Morocco, were analyzed for their microbiota. A total of 81 isolates were obtained and constituted a microbial bank formed of 35 bacteria, 41 yeasts and 5 fungi. The microbial communities have been compared in term of metabolic potential by testing hydrolytic enzymes activities of lipase, protease, amylase, cellulase, pectinase and tannase on agar plate media. The results reveal that among the examined microorganisms, 68 isolates were able to produce at least one of the screened enzymes. The pectinase activity was the predominant one (39.51%), followed by cellulase activity (34.57%) and by lipase activity (27.16%). However, the amylase activity was observed only for 11.11% of the studied isolates, followed by protease activity (9.88%) and by tannase activity 6.17%. Thereby, considering the isolates ability to produce enzymes, they can be considered as potential candidates for industrial and biotechnological applications. Lipases are versatile enzymes that are used widely, it’s why the mostly aim of this work was to isolate new bacterial strains producing high level of lipases with interesting biochemical criteria. Thus, two isolates OR34 and OM2 showed the maximum lipase production under the standard conditions, about 9 U/ml and 11 U/ml, respectively, using pH-stat technique. They were identified as Proteus vulgaris and Serratia marcescens, respectively, via partial 16S rDNA gene sequence analysis.